The frequency of calcium and magnesium differences in recirculation systems for increasing production of mudcrab Scylla serrata seed - Nurussalam, Wildan; Nirmala, Kukuh; Supriyono, Eddy; Hastuti, Yuni Puji (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACTMolting phase is one of many factors that can inhibit mudcrab growth. Recirculation system in culturing mudcrab has a weakness which is the decreasing of ions. Calcium and magnesium in the water can affect the molting phase. The aim of this study was to evaluate the best additional frequency of calcium and magnesium in recirculation system. This research used mudcrab seeds that have weight of 54.856±2.195 gram. This research used completely randomized design with four treatments and three replicates. The treatments were additional frequency of Ca and Mg, comprised of four levels, without additional Ca and Mg (A), additional 30 mg/L Ca and 30 mg/L Mg in every five days (B), additional 30 mg/L Ca, and 30 mg/L Mg in every 10 days (C), and additional 30 mg/L Ca and 30 mg/L Mg in every 15 days (D). The result showed that total of biomass in every treatments were A (379.99±86.16 gram), B (517.65±103.94 gram), C (808.68±59.29 gram), and D (1,054.41±73.54 gram). The highest final biomass was the D treatment (1,054,41±73.54), which was significantly different to others (P<0.05).Keywords: mudcrab, resirculation, calcium, magnesium, molting, production ABSTRAKSalah satu faktor penghambat pertumbuhan kepiting bakau adalah fase molting. Sistem resirkulasi budidaya kepiting bakau memiliki kelemahan yaitu berkurangnya ion-ion. Fase moting pada kepiting bakau sangat dipengaruhi oleh keberadaan ion kalsium dan magnesium dalam air. Penelitian ini bertujuan untuk menentukan frekuensi waktu penambahan kalsium dan magnesium terbaik dalam sistem resirkulasi. Penelitian ini menggunakan benih kepiting bakau dengan berat rata-rata 54,856±2,195 gram. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan empat perlakuan dan tiga ulangan. Perlakuan penambahan Ca dan Mg sebanyak 30 mg/L terdiri atas empat macam frekuensi, yaitu tanpa penambahan Ca dan Mg (A), frekuensi lima hari sekali (B), frekuensi 10 hari sekali (C), dan frekuensi 15 hari sekali (D). Hasil penelitian menunjukkan jumlah biomassa masing-masing perlakuan adalah A (379,99±86,16 gram), B (517,65±103,94 gram), C (808,68±59,29 gram), dan D (1.054,41±73,54 gram). Perlakuan terbaik diperoleh pada perlakuan D dengan jumlah biomassa sebesar (1.054,41±73,54 gram) ini berbeda nyata (P<0,05) dengan perlakuan lainnya. Kata kunci: kepiting bakau, resirkulasi, kalsium, magnesium, molting, produksi